2020
DOI: 10.1088/1755-1315/482/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Studies on heritability and genetic variability for grain physical properties in Malaysian rice germplasm

Abstract: Genetic based information of different traits plays important role in varietal improvement of rice. Twenty rice accessions (Oryza sativa L.) obtained from National Rice Gene Bank were evaluated during main season 2015/2016 to estimate heritability, genetic variability and genetic advance for seven grain physical properties. Among the traits, milled grain length/width ratio, milled grain length, milled grain length after cooking and grain length exhibited high estimates of phenotypic coefficient of variation (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The highest heritability was observed in the DFF trait (97.60%), followed by GWD (80.42%), and GLT (79.78%). Similar results on high H 2 in DFF trait were reported [20;36-41] and high H 2 in GLT and GWD traits were reported by several authors [42][43][44][45][46][47]. High heritability and genetic advance may indicate the role of additive gene action governing a trait.…”
Section: Resultssupporting
confidence: 87%
“…The highest heritability was observed in the DFF trait (97.60%), followed by GWD (80.42%), and GLT (79.78%). Similar results on high H 2 in DFF trait were reported [20;36-41] and high H 2 in GLT and GWD traits were reported by several authors [42][43][44][45][46][47]. High heritability and genetic advance may indicate the role of additive gene action governing a trait.…”
Section: Resultssupporting
confidence: 87%
“…To identify a trait's response to phenotypic selection, heritability is crucial. For a breeding programme to be successful, improving quantitative traits in plants requires accurate heritability estimation [24]. The estimates of genetic advance expressed as a percentage of the mean offer greater confidence about the efficacy of selection in enhancing the traits.…”
Section: Resultsmentioning
confidence: 99%
“…The value of variability and the estimated heritability are essential components that must be measured before determining the method and time for selection (Mustikarini et al 2019). The coefficient of genotypic variation (GCV) and the coefficient of phenotypic variation (PCV) are very useful in determining the amount of diversity that exists in the population and are the basis for variability criteria (Mustikarini et al 2019;Saidon et al 2020). All traits showed high PCV than GCV, similar to the results reported by Srivastava et al (2017); Tiruneh et al (2021), indicating that the variance observed for the traits was more influenced by the genetic factors and suitable environment support the expression of genetic (Kartahadimaja et al 2021).…”
Section: Genetic Variability and Heritability Of Agronomic Traitsmentioning
confidence: 99%